Renaturing historical centres. The role of private space in Milan's green infrastrucutres - Julia Nerantzia Tzortzi; Maria Stella Lux (Agathón)
The symbiosis between vegetation and the built environment in the context of the historic city poses questions and challenges that require a multidisciplinary approach. Today, Urban Green Infrastructure strategies exclude historic centres, where density, preservation constraints, and morphological complexities make it infeasible to apply standardized greening processes focused exclusively on public space. This study aims to provide an assessment of the solutions that are most compatible with historical areas and a methodology to develop green strategies that respect the cultural peculiarities of each context, reconciling the objectives of regeneration with those of cultural heritage enhancement. The ecological potential offered by private spaces is discussed based on the in-depth analysis of the case study focusing on the city of Milan.